2017
DOI: 10.1063/1.4977769
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic wire fabrication process by way of nanoimprint lithography for current induced magnetization switching

Abstract: Nanoimprint lithography (NIL) is an effective method to fabricate nanowire because it does not need expensive systems and this process is easier than conventional processes. In this letter, we report the Current Induced Magnetization Switching (CIMS) in perpendicularly magnetized Tb-Co alloy nanowire fabricated by NIL. The CIMS in Tb-Co alloy wire was observed by using current pulse under in-plane external magnetic field (HL). We successfully observed the CIMS in Tb-Co wire fabricated by NIL. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…19) In our previous study, we have been reported that the J C of CIMS and CIDWM using SOT in rare-earth amorphous perpendicular magnetic materials with low saturation magnetization (M S ) are lower than those in conventional perpendicular magnetic wires because the J C of SOT-CIMS and CIDWM is proportional to the saturation magnetization. [20][21][22][23][24][25][26][27][28][29][30][31][32] In this study, we investigate SOT-CIMS in zero magnetic field by using Gd-Fe alloy and Gd-Fe alloy with IrMn/CoFe multilayered wires. 33)…”
Section: Introductionmentioning
confidence: 99%
“…19) In our previous study, we have been reported that the J C of CIMS and CIDWM using SOT in rare-earth amorphous perpendicular magnetic materials with low saturation magnetization (M S ) are lower than those in conventional perpendicular magnetic wires because the J C of SOT-CIMS and CIDWM is proportional to the saturation magnetization. [20][21][22][23][24][25][26][27][28][29][30][31][32] In this study, we investigate SOT-CIMS in zero magnetic field by using Gd-Fe alloy and Gd-Fe alloy with IrMn/CoFe multilayered wires. 33)…”
Section: Introductionmentioning
confidence: 99%